2022
DOI: 10.1001/jama.2021.20010
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymphadenopathy After COVID-19 Vaccination in a Woman With Breast Cancer

Abstract: A 39-year-old healthy woman without family history of malignancy found a mass in her right breast at 38 weeks of pregnancy. Prior to delivery, she underwent diagnostic ultrasound of the right breast, which showed a possible mass in the location of the palpable lesion that was most consistent with a normal island of fibroglandular tissue. Follow-up mammogram and ultrasound of the right breast (without axillary evaluation) were performed 6 months later, which showed anirregular17-mmmasswithassociatedpleomorphicc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…For patients with cancer, it is recommended that vaccination occurs contralateral to any known adenopathy or tumor pathology. 47,48 Studies have also reported neuropsychiatric symptoms with important morbidity and mortality, such as depression, anxiety, and altered mental status. 46 In very rare instances (approximately 1%), ischemic and hemorrhagic strokes and seizures have been reported.…”
Section: Systemic Reactions-immune Mediatedmentioning
confidence: 99%
“…For patients with cancer, it is recommended that vaccination occurs contralateral to any known adenopathy or tumor pathology. 47,48 Studies have also reported neuropsychiatric symptoms with important morbidity and mortality, such as depression, anxiety, and altered mental status. 46 In very rare instances (approximately 1%), ischemic and hemorrhagic strokes and seizures have been reported.…”
Section: Systemic Reactions-immune Mediatedmentioning
confidence: 99%
“…At the time of follow-up US, the adenopathy had resolved in 54/91 (59%) of patients. Patients with resolved adenopathy had longer times between vaccination and US (16 weeks [7–24] versus 10 weeks [4–18], p = 0,04) and between MRI and US (5 weeks [2–9] versus 2 weeks, 1. , 2.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 vaccine has been shown to cause unilateral axillary adenopathy. 1 With increasing COVID-19 vaccine availability and recommendations for additional booster vaccinations to combat COVID-19 variants, the medical community will continue to be challenged with management recommendations for axillary adenopathy in the setting of a recent COVID-19 vaccine. In breast imaging, unilateral axillary adenopathy is typically considered suspicious for locally advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lengthening imaging follow-up to 12-16 weeks after the second dose may reduce unnecessary biopsy recommendations. 25 Lam and Flanagan [ 34 ] Axillary lymphadenopathy after COVID-19 vaccination in a woman with breast cancer. Case report of a 39-year-old woman with known right breast malignancy who underwent MRI before lumpectomy, showing right axillary LAP does not present on prior imaging.…”
Section: Tablementioning
confidence: 99%